Synthesis of biomass waste derived activated carbon-NBR composites for automobile application - Jadhav, A.; Mohanraj, G.T.; Gokarn, A.; Mayadevi, S. (Chemistry and Chemical Technology, 2018)
This paper reports on usability of activated carbon obtained from areca nut shell, coconut shell, and coconut leaves as a filler to prepare NBR based composite for automobile based application. The carbon was activated by phosphoric acid (H3PO4) as dehydrating agent. The stoichiometric ratio of biomass and phosphoric acid was found to be 3:1 for the batch size of 300 g. As compared to commercially available carbon filler, the activated carbon derived from biomass waste responded better to the petrol swelling test. Among three biomass waste sources, namely, areca nut shell, coconut shell, and coconut leaves, activated carbon derived from coconut shell was appeared to be the best for percent swelling and percent deviation in hardness. The results obtained are confirmed by proximate analysis.
Keywords: activated carbon; composites; hardness; NBR; Phosphoric acid

Ferets diameter estimation of activated carbon for effluent treatment application - Jadhav, Abhijit; Mohanraj, Govindraj; Gokarn, Ashok; Mayadevi, Susheeladevi (Journal of the Indian Chemical Society, 2019)
In this paper, activated carbon was produced of by chemical activation with phosphoric acid of agricultural wastes such as Arecanut shell of 25 micronmeter at 400 degrees C by slow pyrolysis. The BET surface area and iodine number surface area is calculated and compared. The FTIR spectra show the presence of activated carbon. The TGA revealed, activated carbon is thermally stable at 480 degrees C. The SEM shows the incorporation of activated carbon particles leads to the systematic change in morphology of activated carbon. Surface area plot shows the details of morphological change caused by iodine number surface area. Ferets diameter is estimated to know circularity of the particle. Methylene blue number, acid adsorption value is calculated to know adsorption capacity of the carbon. Thus results proves selection of ferets diameter, activation temperature, and impregnation ratio is important in determining the quality of activated carbon obtained and its use in industrial waste water treatment.
Keywords: activated carbon; Arecanut shell; Phosphoric acid; teret diameter